2014
DOI: 10.1111/ibi.12134
|View full text |Cite
|
Sign up to set email alerts
|

Early springs and breeding performance in two sympatric duck species with different migration strategies

Abstract: The capacity of migratory species to adapt to climate change may depend on their migratory and reproductive strategies. For example, reproductive output is likely to be influenced by how well migration and nesting are timed to temporal patterns of food abundance, or by temperature variations during the brood rearing phase. Based on two decades (1988–2009) of waterfowl counts from a boreal catchment in southern Finland we assessed how variation in ice break‐up date affected nesting phenology and breeding succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…The finding that local increases were associated with early breed- Among European ducks, it has been found that mallard, common teal, and common goldeneye, which are all early-nesting species, are capable of adjusting their timing of breeding to temporal variation in spring thaw (Arzel et al, 2014;Clark, Pöysä, Runko, & Paasivaara, 2014;Oja & Pöysä, 2007). With this capacity in mind, and considering that ice-out dates of lakes have advanced in northern Europe (e.g.…”
Section: Early Breeders Did Better Than Late Breedersmentioning
confidence: 99%
“…The finding that local increases were associated with early breed- Among European ducks, it has been found that mallard, common teal, and common goldeneye, which are all early-nesting species, are capable of adjusting their timing of breeding to temporal variation in spring thaw (Arzel et al, 2014;Clark, Pöysä, Runko, & Paasivaara, 2014;Oja & Pöysä, 2007). With this capacity in mind, and considering that ice-out dates of lakes have advanced in northern Europe (e.g.…”
Section: Early Breeders Did Better Than Late Breedersmentioning
confidence: 99%
“…On the other hand, Arzel et al (2014) did not find adverse effects of precipitation and low temperature during the first week after hatching on brood size, a measure of breeding success, in mallard and teal in a study conducted in southern Finland.…”
Section: Discussionmentioning
confidence: 75%
“…Finally, the ability of migratory species to adapt to climate change may depend on their movement ecology (Arzel et al 2014). The majority (85%) of precipitation in the Sahel of West Africa falls from July to September (Zwarts et al 2009), and climate-induced changes to temperatures and the frequency, timing and quantity of rainfall may greatly alter their habitat availability.…”
Section: Discussionmentioning
confidence: 99%